Stability Testing of an Air Quality Monitoring System for Particulate Matter (PM2.5 and PM10) Based on The SEN0233 Sensor - Afifah, Anshah Silmi; Nugroho, Alfani Risman; Widiyanto, Wahyu; Haryati, Putri Dwi; Syah, Edo Ardiyan (Journal of Engineering Science and Technology Management, 2025)
Particulate Matter (PM) is an air pollutant that has the potential to pose serious health risks to the public, including respiratory and cardiovascular diseases. This study aims to design and develop a real-time monitoring system for PM2.5 and PM10 using the SEN0233 sensor. This system is expected to be able to provide accurate data on the concentration of particles in the air. The research methodology includes selecting the right sensor, designing a NodeMCU microcontroller-based system, and testing the sensor to ensure measurement accuracy. The collected data will be stored in a database and can be accessed through a web interface, allowing users to monitor air quality directly. Initial test results show that the SEN0233 sensor is able to detect PM2.5 and PM10 concentrations well. This research contributes to the development of a more efficient and reliable monitoring system, to improve air quality and overall public health.